2017
DOI: 10.1128/aac.02520-16
|View full text |Cite
|
Sign up to set email alerts
|

The Carbapenemase-Producing Klebsiella pneumoniae Population Is Distinct and More Clonal than the Carbapenem-Susceptible Population

Abstract: We studied in parallel the population structure of 90 carbapenemase-producing and 88 carbapenemase-susceptible isolates collected in 20 Spanish hospitals, in the context of the EuSCAPE project. Fourteen and 50 multilocus sequence types (MLSTs) were detected among the carbapenemase-producing and carbapenem-susceptible isolates, respectively. ST11 and ST15 clones were more frequent in the carbapenemase-producing group than in the carbapenemase-susceptible group ( < 0.0001). Among the members of the carbapenem-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…It has been reported that carbapenemase producing K. pneumoniae strains have a different population and less genetic diversity as compared to carbapenem susceptible isolates [26]. In our study, ERIC-PCR showed five clusters and higher genetic homogeneity among bla NDM-1 producers as compared to negative ones.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that carbapenemase producing K. pneumoniae strains have a different population and less genetic diversity as compared to carbapenem susceptible isolates [26]. In our study, ERIC-PCR showed five clusters and higher genetic homogeneity among bla NDM-1 producers as compared to negative ones.…”
Section: Discussionsupporting
confidence: 56%
“…These CGs contain several high-risk international clones including ST11, ST258 and ST15 4,5 . Although recent studies have not described ST15 as a widespread clonal lineage 6 , other data indicates that ST15 is a pan-drug resistant widespread clone, frequently associated with carbapenemase production 7 and nosocomial infections. ST15 was recently identified in the USA 8 , Brazil 9 , China 10,11 , Taiwan 12 , and several European countries 13 including Portugal 14 , Belgium 15 , Bulgaria 16 and Hungary 4 .…”
Section: Identification Of a Newly Isolated Lytic Bacteriophage Againmentioning
confidence: 95%
“…However, in spite of the close proximity of the two hospitals, these ST405 isolates were found to have different PFGE patterns (data not shown), suggesting independent introduction events. In a study published in 2017 by the national reference laboratory that included data representing K. pneumoniae isolates collected in different Spanish areas, both sequence types were found among the most prevalent ones, highlighting their persistence over time in our country (25).…”
Section: Discussionmentioning
confidence: 72%